THE POTENTIAL OF PALM SHELL ACTIVATED CARBON AS AN ADSORBENT FOR HEAVY METALS IN THE RECYCLING PROCESS OF USED LUBRICATING OIL - Safni; Zilfa, Zilfa; Amanda, Selya (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
With the increasing industrial and transportation activities, the demand for lubricating oil is increasing every year. Lubricating oil is used to reduce friction and wear on frictional engine components. Over time, lubricating oil becomes inefficient and needs to be replaced with new oil. To enhance the efficiency of petroleum use and reduce environmental pollution, used lubricants need to be recycled. One method of improving the quality of used lubricants is by absorbing heavy metal contaminants using activated carbon from palm kernel shells. The efficiency of activated carbon adsorption as an adsorbent for heavy metals in used lubricants was observed by varying the adsorption parameters of contact time, adsorbent mass, and sample volume. In this study, the absorption of several heavy metals, including iron (Fe), lead (Pb), and zinc (Zn), was investigated. Analysis of the absorption results was performed using AAS, FTIR, XRD, and XRF. The results showed that the absorption of metals in used lubricants using activated carbon from palm kernel shells with optimum parameters can absorb 90% of Fe, Pb, and Zn metals. The optimum contact time for each metal adsorption was 3 hours, with an adsorbent mass of 0.75 grams and a sample volume of 5 mL. Analysis of used lubricants before and after adsorption using FTIR indicated a shift in wave numbers, indicating an adsorption process.